"Do Not Protect Us, Train Us."—Swiss Healthcare Students' Attitudes Toward Caring for Terminally Ill Patients. (March 2023) - Juvet, Typhaine Maïko; Bornet, Marc-Antoine; Desbiens, Jean-François; Tapp, Diane; Roos, Pauline
Positive attitudes and a sense of competence toward end-of-life care are the key to adequately support terminally ill patients. This qualitative study aims to explore healthcare students' attitudes toward caring for terminally ill patients. Eleven students from the University of Applied Health Sciences in Switzerland participated in focus groups. Attitudes were overall positive. Most participants felt that supporting dying patients was a way to achieve professional fulfillment. However, most students felt not competent in palliative care and lacking experience. They wanted to receive better training, more specifically in good practices and appropriate behaviors. Our study fills a knowledge gap regarding the opinions and pedagogical needs of healthcare students, and highlights the importance of experiencing end-of-life care during the educational process. We recommend early exposure to terminally ill patients and appropriate attitudes toward death and dying as part of the bachelor's curriculum, accompanied by benevolent guidance from teachers and health professionals.